2013
DOI: 10.1007/s10072-013-1580-9
|View full text |Cite
|
Sign up to set email alerts
|

Homozygosity and severity of phenotypic presentation in a CADASIL family

Abstract: Most of causative mutations of the cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) are missense point mutations either creating or deleting one cysteine residue, inherited in a heterozygous state. Only few homozygous patients are reported to date and some of them showed phenotypic peculiarities. We here describe a CADASIL family in which a member showed homozygous mutation and compare its clinical profile with five subjects throughout three generation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…16 Although neither in-depth genealogical reconstruction nor haplotype analysis were performed in the APP mutation carriers belonging to this pedigree, we hypothesize that they are related to families previously described and probably originated from the same common ancestor before the 19th century. 16 In this study, AD behaves as a real dominant disease, similar to that reported for the rare homozygous CADASIL patients 39,40 and differently from that reported in the AD family with the recessive APP A673V mutation, 7 which causes disease only in the homozygous state, whereas heterozygous carriers were unaffected, consistent with a recessive trait of inheritance. All these data confirm that genetic AD may be considered a disease with dominant and recessive traits of inheritance, thus demonstrating the importance to search for recessive AD loci, for instance by analyzing homozygosity in consanguineous families and inbred populations.…”
supporting
confidence: 73%
“…16 Although neither in-depth genealogical reconstruction nor haplotype analysis were performed in the APP mutation carriers belonging to this pedigree, we hypothesize that they are related to families previously described and probably originated from the same common ancestor before the 19th century. 16 In this study, AD behaves as a real dominant disease, similar to that reported for the rare homozygous CADASIL patients 39,40 and differently from that reported in the AD family with the recessive APP A673V mutation, 7 which causes disease only in the homozygous state, whereas heterozygous carriers were unaffected, consistent with a recessive trait of inheritance. All these data confirm that genetic AD may be considered a disease with dominant and recessive traits of inheritance, thus demonstrating the importance to search for recessive AD loci, for instance by analyzing homozygosity in consanguineous families and inbred populations.…”
supporting
confidence: 73%
“…This mode of pathogenesis suggests that CADASIL-causing NOTCH3 mutations are not loss of function; rather they are likely neomorphic or toxic. This is further supported by the observation that patients harboring homozygous CADASIL mutations experience similar or only slightly more severe symptoms (Abou Al-Shaar et al, 2016;Liem et al, 2008;Pippucci et al, 2015;Ragno et al, 2013;Soong et al, 2013;Tuominen et al, 2001;Vinciguerra et al, 2014); if the mutations were loss of function, homozygous patients would be expected to suffer more severe consequences. Interestingly, previous reports have described a clustering of CADASIL-related NOTCH3 mutations in exon 4 ( Fig.…”
Section: Notch3 In Development: a Cornucopia Of Congenital Disordersmentioning
confidence: 81%
“…At present, five patients with homozygous cysteine mutations in NOTCH3 [Tuominen et al : p.Arg133Cys , Liem et al : p.Arg578Cys , Ragno et al : p.Gly528Cys , Soong et al : p.Arg544Cys and Vinciguerra et al : p.Cys183Ser ] have been reported.…”
Section: Genetics and Biochemistrymentioning
confidence: 99%